Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1634/theoncologist.2018-0590
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Toxicities During Chemotherapy Regimens in Current Clinical Practice for Early Breast Cancer

Abstract: Background This study explores the incidence of patient‐reported major toxicity—symptoms rated “moderate,” “severe,” or “very severe”—for chemotherapy regimens commonly used in early breast cancer. Patients and Methods Female patients aged 21 years or older completed a validated Patient‐Reported Symptom Monitoring instrument and rated 17 symptoms throughout adjuvant or neoadjuvant chemotherapy. Fisher's exact tests compared differences in percentages in symptom ratings, and general linear regression was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
57
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 56 publications
9
57
0
6
Order By: Relevance
“…In this study, we conducted an analysis among women with early‐stage breast cancer in which we compared clinician‐reported (CTCAE) and patient‐reported (PRO‐CTCAE) severity for 17 symptoms collected at multiple time points throughout chemotherapy. We have previously reported that patient‐assessed symptom severity for these 17 symptoms varies significantly among 4 chemotherapy regimens commonly used in current clinical practice, 17 and this confirms the importance of continuous symptom monitoring throughout treatment. We have also reported that there is minimal agreement between patient‐ and clinician‐reported severity scores for chemotherapy‐induced peripheral neuropathy associated with these chemotherapy regimens 18 .…”
Section: Introductionsupporting
confidence: 59%
“…In this study, we conducted an analysis among women with early‐stage breast cancer in which we compared clinician‐reported (CTCAE) and patient‐reported (PRO‐CTCAE) severity for 17 symptoms collected at multiple time points throughout chemotherapy. We have previously reported that patient‐assessed symptom severity for these 17 symptoms varies significantly among 4 chemotherapy regimens commonly used in current clinical practice, 17 and this confirms the importance of continuous symptom monitoring throughout treatment. We have also reported that there is minimal agreement between patient‐ and clinician‐reported severity scores for chemotherapy‐induced peripheral neuropathy associated with these chemotherapy regimens 18 .…”
Section: Introductionsupporting
confidence: 59%
“…A large proportion of patients receive adjuvant chemotherapy as treatment in addition to surgery. During chemotherapy side-effects such as fatigue, myalgia, nausea, diarrhoea and peripheral neuropathy are common [2].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to measure changes in energy, stress, nausea and pain immediately after a single session of aerobic or endurance training within the first week after chemotherapy. Additional aims were to study if potential changes were [1] related to type of training (aerobic or endurance) and [2] previous exercise habit, and if the [3] changes remained 3 hrs after training was completed.…”
Section: Introductionmentioning
confidence: 99%
“…1 Common cancer treatments, such as chemotherapy, lead to side effects during treatment such as nausea, peripheral neuropathy and cancer-related fatigue. 2 Survivors also live with treatment-related side effects, including fatigue, pain, loss of strength and anxiety, for years after their treatments have ended. 1 3 4…”
Section: Introductionmentioning
confidence: 99%